FORMATION OF CREATIVE PROFESSIONAL PERSONALITY OF NONLINGUISTIC HIGHER EDUCATION ESTABLISHMENT STUDENT IN FOREIGN LANGUAGE COURSE - Tatiana E. Zmeeva (Высшее образование в России)
The article is devoted to the formation of creative professional personality of nonlinguistic higher education establishment student, in particular, in course of foreign language for professional communication purposes. The author analyzes existing approaches to the definition of the concepts of "creativity", "autonomy", "independent work", "creative autonomy". Students' independent work is seen as a means of developing autonomy and is not identified with the notion of independent activity, which is treated as a result of autonomy and as an independent creative activity. Analyzing an example of the organization of independent educational and cognitive activity of students in foreign language course for professional communication the author demonstrates the possible phases of a dialectical transition from independent work to independent creative activity of students, identifies the necessary conditions of efficiency of process of forming the creative autonomy of the future specialist.